Physiological impact of flavonoids on nodulation and ureide metabolism in legume plants - Bosse, Marco Antônio [UNESP]; Silva, Mariana Bocchi da [UNESP]; Oliveira, Natália Gabriela Rós Marques de [UNESP]; Araujo, Maycon Anderson de [UNESP]; Rodrigues, Cleverson [UNESP]; Azevedo, Jaquelyne Poliszuk de [UNESP]; Reis, André Rodrigues dos [UNESP] (Elsevier, 2021)
Legume plants from Fabaceae family (phylogenetic group composed by three subfamilies: Caesalpinioideae, Mimosoideae, and Papilionoideae) can fix atmospheric nitrogen (N2) into ammonia (NH3) by the symbiotic relationship with rhizobia bacteria. These bacteria respond chemotactically to certain compounds released by plants such as sugars, amino acids and organic acids. Root secretion of isoflavonoids acts as inducers for nod genes in rhizobia and ABC transporters and ICHG (isoflavone conjugates hydrolyzing beta-glucosidase) at apoplast are related to the exudation of genistein and daidzein in soybean roots. Biological nitrogen fixation (BNF) occurs inside the nodule by the action of nitrogenase enzyme, which fixes N2 into NH3, which is converted into ureides (allantoin and allantoic acid). In this review, we bring together the latest findings on flavonoids biosynthesis and ureide metabolism in several legume plant species. We emphasize how flavonoids induce nod genes in rhizobia, affecting chemotaxis, nodulation, ureide production, growth and yield of legume plants. Mainly, isoflavonoids daidzein and genistein are responsible for nod genes activation in the rhizobia bacteria. Flavonoids also play an important role during nodule organogenesis by acting as auxin transporter inhibitors in root cells, especially in indeterminate nodules. The ureides are the main N transport form in tropical legumes and they are catabolized in leaves and other sink tissues to produce amino acids and proteins needed for plant growth and yield.
Keywords: Allantoic acid; Allantoin; Chemotaxis; Nitrogen fixation; Rhizobium